Tumor-infiltrating lymphocytes in cancer immunotherapy: from chemotactic recruitment to translational modeling - Kraja, Fatjona Pupuleku; Jurisic, Vladimir B.; Hromić-Jahjefendić, Altijana; Rossopoulou, Nafsika; Katsila, Theodora; Mirjacic Martinovic, Katarina; De Las Rivas, Javier; Diaconu, Carmen Cristina; Szöőr, Árpád (Frontiers in Immunology, 2025)
Tumor-infiltrating lymphocytes (TILs) are a diverse population of immune cells that play a central role in tumor immunity and have emerged as critical mediators in cancer immunotherapy. This review explores the phenotypic and functional diversity of TILs—including CD8+ cytotoxic T cells, CD4+ helper T cells, regulatory T cells, B cells, and natural killer (NK) cells—and their dynamic interactions within the tumor microenvironment (TME). While TILs can drive tumor regression, their activity is often hindered by immune checkpoint signaling, metabolic exhaustion, and stromal exclusion. We highlight TIL recruitment, activation, and polarization mechanisms, focusing on chemokine gradients, endothelial adhesion molecules, and dendritic cell-mediated priming. Special emphasis is placed on preclinical models that evaluate TIL function, including 3D tumor spheroids, organoid co-cultures, syngeneic mouse models, and humanized systems. These provide valuable platforms for optimizing TIL-based therapies. Furthermore, we examine the prognostic and predictive value of TILs across cancer types, their role in adoptive cell therapy, and the challenges of translating preclinical success into clinical efficacy. Emerging technologies such as single-cell sequencing, neoantigen prediction, and biomaterial platforms are transforming our understanding of TIL biology and enhancing their therapeutic potential. Innovative strategies—ranging from genetic engineering and combination therapies to targeted modulation of the TME—are being developed to overcome resistance mechanisms and improve TIL persistence, infiltration, and cytotoxicity. This review integrates current advances in TIL research and therapy, offering a comprehensive foundation for future clinical translation. TILs hold significant promise as both biomarkers and therapeutic agents, and with continued innovation, they are poised to become a cornerstone of personalized cancer immunotherapy.